Innovative Use of Chrome-Containing Waste and Jute Fiber in the Production of Biodegradable Therapeutic Insole (Indian Journal of Fibre & Textile Research (IJFTR), 2026)
This study explores the potential of converting chrome-containing waste (CCW) and jute fiber (JF) into usable products by creating foot pressure composite (FPC). Foot pressure composite (FPC) was produced using leather-based composite (LBC) and characterized using functional, thermal, morphological, mechanical, and biodegradation properties. Plantar pressure measurement analysis on healthy people wearing FPC demonstrated an increase in plantar pressure effect for the foot. The results showed that FPC was advantageous compared to normal insoles, providing beneficial pressure effects and possessing the necessary mechanical properties for FPC production. Additionally, FPC was found to be biodegradable. This study demonstrates that CCW and JF can be repurposed into cost-effective, therapeutic footwear, generating income, reducing environmental pollution, and offering a viable waste recycling technology.